Amplification-free and direct fluorometric determination of telomerase activity in cell lysates using chimeric DNA-templated silver nanoclusters - Lee, Shi Ting; Rahman, Ruman; Muthoosamy, Kasturi; Mohamed, Nur Aliana Hidayah; Su, XiaoDi; Tayyab, Saad; New, Siu Yee (Springer Verlag (Germany), 2019)
A fluorogenic probe has been developed for determination of telomerase activity using chimeric DNA-templated silver nanoclusters (AgNCs). The formation of AgNCs was investigated before (route A) and after (route B) telomerase elongation reaction. Both routes caused selective quenching of the yellow emission of the AgNCs (best measured at excitation/emission wavelength of 470/557 nm) in telomerase-positive samples. The quenching mechanism was studied using synthetically elongated DNA to mimic the telomerase-catalyzed elongation. The findings show that quenching is due to the formation of parallel G-quadruplexes with a -TTA- loop in the telomerase elongated products. The assay was validated using different cancer cell extracts, with intra- and interassay coefficients of variations of <9.8%. The limits of detection for MCF7, RPMI 2650 and HT29 cell lines are 15, 22 and 39 cells/μL. This represents a distinct improvement over the existing telomeric repeat amplification protocol (TRAP) assay in terms of time, sensitivity and cost. Graphical Abstract A method was developed using chimeric DNA-templated silver nanoclusters to detect telomerase activity directly in cell extracts. The sensitivity of this new method outperforms the traditional TRAP assay, and without the need for amplification.